CSR Practices in Food and Beverage Companies During Pandemic - Handayati, Puji; Wafaretta, Vega; Anugrahani, Inanda Shinta; Fauzan, Slamet (AIBPM Publisher, 2021)
The covid-19 pandemic affects businesses facing the dilemma between the company's health and risks. This study aims to investigate the practice of CSR of food and beverage companies in Malang on the economic and social dimensions before and during the pandemic. The survey was conducted by distributing questionnaires directly to the managers or owners of the companies. Thirty questionnaires were descriptively analyzed. The results of this study indicate that some companies in Malang increase their CSR quality during the pandemic, such as by adding CSR quantity, implementing health protocols inside their restaurants, maintaining product cleanliness, giving more attention to employees' health, and increasing more alms by distributing masks and vitamins to customers and the public.